2010
DOI: 10.1111/j.1758-2229.2009.00092.x
|View full text |Cite
|
Sign up to set email alerts
|

Rapid in situ detection of virulent Vibrio vulnificus strains in raw oyster matrices using real‐time PCR

Abstract: Vibrio vulnificus is a Gram-negative bacterial pathogen responsible for the vast majority of bacterially mediated fatalities from the consumption of raw or undercooked seafood in the USA. Vibrio vulnificus-associated septicaemia can occur rapidly (< 24 h); however, methods for the isolation and confirmation of V. vulnificus from seafood samples typically require several days. A real-time PCR assay was developed for V. vulnificus biotype 1 that provides a rapid means of identifying a gene fragment (vcgC) previo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 18 publications
1
34
1
Order By: Relevance
“…The species specificity of the real-time PCR assay was evaluated by testing pathogenic and non-pathogenic V. vulnificus strains (deemed pathogenic to humans based on previous human serum reactivity analysis), as well as a range of closely and distantly related bacteria. To compare pilF with established pathogenicity analysis we analysed strains using vcgC realtime PCR, an assay previously shown to successfully identify pathogenic biotype 1 V. vulnificus isolates (Baker-Austin et al, 2010b). In agreement with previous work (Roig et al, 2010), the results here demonstrated that the pilF was capable of correctly identifying the vast majority of human serum-resistant strains, irrespective of biotype (Table 2).…”
Section: Resultssupporting
confidence: 71%
See 3 more Smart Citations
“…The species specificity of the real-time PCR assay was evaluated by testing pathogenic and non-pathogenic V. vulnificus strains (deemed pathogenic to humans based on previous human serum reactivity analysis), as well as a range of closely and distantly related bacteria. To compare pilF with established pathogenicity analysis we analysed strains using vcgC realtime PCR, an assay previously shown to successfully identify pathogenic biotype 1 V. vulnificus isolates (Baker-Austin et al, 2010b). In agreement with previous work (Roig et al, 2010), the results here demonstrated that the pilF was capable of correctly identifying the vast majority of human serum-resistant strains, irrespective of biotype (Table 2).…”
Section: Resultssupporting
confidence: 71%
“…No amplification of closely related vibrio or non-vibrio strains were observed, indicating the specificity of the pilF realtime PCR assay ( Table 2). The pilF assay thus contrasts with other targets used to identify pathogenic strains of V. vulnificus, such as 16S rRNA (Aznar et al, 1994;Nilsson et al, 2003;Vickery et al, 2007) and vcgC polymorphisms (Rosche et al, 2005;Warner and Oliver, 2008;Baker-Austin et al, 2010b), which have shown limited usefulness in detecting biotype 2 and biotype 3 V. vulnificus strains potentially dangerous to human health (Roig et al, 2010;Sanjuan et al, 2009). Both biotype 2 (serovar E and serovar I) and biotype 3 V. vulnificus strains represent important human pathogens (Amaro and Biosca, 1996;Bisharat et al, 1999), and the ability to identify potentially virulent strains rapidly is of paramount importance.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…vulnificus and V. vulnificus infections have been reported throughout Europe, Scandinavia, South America, the Far East, South Pacific, as well as on all coasts of the United States (15). Along with oysters and other molluscan bivalves and estuarine/coastal waters, V. vulnificus has been reported in fish (82,83,84), sediments (85,86), and plankton (73). The presence of this pathogen appears to be spreading to areas where it was not previously reported, and this is likely due to global warming (see below).…”
Section: Geographic Distributionmentioning
confidence: 82%